2015
DOI: 10.1371/journal.pone.0118871
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of HIV Viraemic Controllers and Noncontrollers with Normal CD4 Counts Is Exclusively Determined by Antigen-Specific CD8+ T-Cell-Mediated HIV Suppression

Abstract: In this cross-sectional study we evaluated T-cell responses using several assays to determine immune correlates of HIV control that distinguish untreated viraemic controllers (VC) from noncontrollers (NC) with similar CD4 counts. Samples were taken from 65 ART-naïve chronically HIV-infected VC and NC from Thailand with matching CD4 counts in the normal range (>450 cells/μl). We determined HIVp24-specific T-cell responses using standard Interferon-gamma (IFNγ) ELISpot assays, and compared the functional quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Indeed, analysis of untreated patients with poor HIV control (progressors) and those with HIV control (nonprogressors) demonstrated that nonprogressors possessed higher functionality than progressors (39). More recently, suppression of HIV replication, through killing of HIV-infected targets by high avidity CD8 + T cells (40) was found to be the exclusive determinant of HIV viremic control in progressors (41), suggesting that CD8 + T cell avidity, rather than polyfunctionality, may also underlie HIV control. Similarly, experimental manipulation of TCR avidity employing adoptive transfer of T cells genetically engineered to express TCRs of varying affinities to the melanoma antigen gp100 demonstrated that antitumor efficacy was determined by TCR affinity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of untreated patients with poor HIV control (progressors) and those with HIV control (nonprogressors) demonstrated that nonprogressors possessed higher functionality than progressors (39). More recently, suppression of HIV replication, through killing of HIV-infected targets by high avidity CD8 + T cells (40) was found to be the exclusive determinant of HIV viremic control in progressors (41), suggesting that CD8 + T cell avidity, rather than polyfunctionality, may also underlie HIV control. Similarly, experimental manipulation of TCR avidity employing adoptive transfer of T cells genetically engineered to express TCRs of varying affinities to the melanoma antigen gp100 demonstrated that antitumor efficacy was determined by TCR affinity (33).…”
Section: Discussionmentioning
confidence: 99%
“…This capacity was not found in cART-treated or untreated viremic HIV-1 patients, either during the acute or chronic phase of infection (38)(39)(40)(41). HIV-1 suppression assays provide the most robust method to distinguish between the functional capacities of CD8 + T cells from HIV-1 controllers and noncontrollers (40,42,43). We thus sought to adapt this in vitro assay to the study of HIV-2 using an SBL virus strain (20), with supernatant p27 concentration as a readout.…”
Section: Unstimulated Cd8 + T Cells From Hiv-2 Controllers Suppress Hmentioning
confidence: 99%
“…CD8 + T-cells from HICs typically suppress ex vivo infection of autologous CD4 + T-cells (Angin et al, 2016; Buckheit et al, 2012; Julg et al, 2010; Saez-Cirion et al, 2007; Saez-Cirion et al, 2009; Tansiri et al, 2015). We therefore investigated this property as a potential discriminant between SICs and VIRs.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity of CD8 + T-cells to suppress infection of autologous CD4 + T-cells directly ex vivo is a particular feature of HICs (Almeida et al, 2009; Angin et al, 2016; Buckheit et al, 2012; Julg et al, 2010; Saez-Cirion et al, 2007; Saez-Cirion et al, 2009; Tansiri et al, 2015) that is mediated by the rapid elimination of infected CD4+ T-cells (Saez-Cirion et al, 2007). Irrespective of subsequent outcome, we detected relatively weak CD8 + T-cell-mediated SIV-suppressive activity during primary infection, despite the vigorous mobilization of SIV-specific CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation